The Art Requisitions by the French under Napoléon and the Detachment of Frescoes in Rome, with an Emphasis on Raphael - Cathleen Hoeniger (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The restoration of Italian paintings at the Louvre, after their confiscation by Napoleon’s deputies, has received considerable attention; however, the concurrent preoccupation of the French in Rome with the detachment of frescoes has been little studied, even though the desire for Raphael’s art led some to plan the extraction of his Stanze frescoes. In this essay, the parallel practices of the transfer method on Raphael’s altarpieces in Paris and the detachment of frescoes by close followers of Raphael and Michelangelo in Rome will be explored in light of the innovations of the age in science and technology. The willingness of the relatively inexperienced French to take substantial risks will be contrasted with the more cautious conservatism of Italian restorers, and special focus will be placed on Palmaroli’s involvement in the detachment and restoration of Daniele da Volterra’s famous Deposition.